A Preliminary Investigation on the Role of Hemicellulose in Hydrothermal Carbonization with Recycled Process Water - Antonio Picone; Chiara Corrado; Antonio Messineo; Maurizio Volpe (Chemical Engineering Transactions)
Hydrothermal carbonization (HTC) is a promising thermochemical technology to upgrade biomass waste into valuable solid bio-fuels and functionalized carbon materials for various applications. In order to better govern the process, the complex reaction pathways involved in the hydrochar formation need to be more deeply investigated and understood. In this work, the influence of hemicellulose on HTC with recycled process water was studied and preliminary results were reported. Commercially available microcrystalline xylose and cellulose were separately treated at different reaction severity conditions and the effect of process water (PW) recycling on HTC of cellulose was assessed in terms of mass yield computation, secondary char (SC) extraction and hydrochars properties. For all HTC conditions tested, hydrochar and gas mass yields increased with PW recirculation. SC formation was remarkably enhanced with the increase of conversion severity, when PW from xylose was used as a solvent; correspondingly, a slight increase in the hydrochars’ energy content was also found.